PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS KAHOOT UNTUK MENINGKATKAN KOMPETENSI PEDAGOGI GURUJUDUL ARTIKEL - Darojah, Rofiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the pedagogical competence of elementary school teachers in Lebaksiu District through the development of interactive multimedia based on Kahoot. The method used is Research and Development (R&D), covering needs analysis, design, development, expert validation, and limited trials through classroom observation. The observation instrument assessed aspects such as lesson planning, teaching strategies, content mastery, technology use, student engagement, and evaluation. Validation results using Aiken’s V indicated that the materials and media were in the appropriate to highly appropriate category. Classroom observations showed increased student engagement and media effectiveness, although some technical aspects still need refinement. Overall, Kahoot-based multimedia proved effective and can serve as an innovative and engaging learning tool in elementary education.